SDHA related tumorigenesis: a new case series and literature review for variant interpretation and pathogenicity. Issue 3 (2nd March 2017) - Casey, Ruth T.; Ascher, David B.; Rattenberry, Eleanor; Izatt, Louise; Andrews, Katrina A.; Simpson, Helen L.; Challis, Benjamen; Park, Soo‐Mi; Bulusu, Venkata R.; Lalloo, Fiona; Pires, Douglas E. V.; West, Hannah; et al.
Abstract: Purpose: To evaluate the role of germline SDHA mutation analysis by (1) comprehensive literature review, (2) description of novel germline SDHA mutations and (3) in silico structural prediction analysis of missense substitutions in SDHA. Patients and methods: A systematic literature review and a retrospective review of the molecular and clinical features of patients identified with putative germline variants in UK molecular genetic laboratories was performed. To evaluate the molecular consequences of SDHA missense variants, a novel model of the SDHA/B/C/D complex was generated and the structural effects of missense substitutions identified in the literature, our UK novel cohort and a further 32 "control missense variants" were predicted by the mCSM computational platform. These structural predictions were correlated with the results of tumor studies and other bioinformatic predictions. Results: Literature review revealed reports of 17 different germline SDHA variants in 47 affected individuals from 45 kindreds. A further 10 different variants in 15 previously unreported cases (seven novel variants in eight patients) were added from our UK series. In silico structural prediction studies of 11 candidate missense germline mutations suggested that most (63.7%) would destabilize the SDHA protomer, and that most (78.1%) rare SDHA missense variants present in a control data set (ESP6500) were also associated with impaired protein stability. Conclusion: The clinical spectrum of SDHA ‐associated neoplasia differs from that of germline mutations in other SDH‐subunits. The interpretation of the significance of novel SDHA missense substitutions is challenging. We recommend that multiple investigations (e.g. tumor studies, metabolomic profiling) should be performed to aid classification of rare missense variants before genetic testing results are used to influence clinical management. Abstract : This study investigates the role of germline SDHA mutation analysis by (1) comprehensive literature review, (2) description of novel germline SDHA mutations and (3) in silico structural prediction analysis of missense substitutions in SDHA.